Pengaruh model pembelajaran group investigation terhadap pemahaman konsep matematis siswa SD - Hartiani, Devi; Eka Putri, Hafiziani; Iskandar, Sofyan (COLLASE (Creative of Learning Students Elementary Education), 2024)
The importance of understanding the concept because understanding is a fundamental ability that students must have to learn more advanced concepts, so that students can develop their abilities. The purpose of this study was to determine the effect of the Investigation learning model on elementary students' understanding of mathematical concepts. This research is included in the quasi-experimental research with nonequivalent control group design. This design divides into two classes, namely the experimental class and the control class. Based on the research results, there is a significant influence from the use of the Group Investigation learning model of 71.6%. So that the Group Investigation learning model has an influence on students' understanding of mathematical concepts. This can be seen from the average n-gain score in the experimental class of 0.601 while the average n-gain in the control class is 0.442. In the interpretation of the average n-gain of the two classes it has moderate criteria, but the average score of the experimental class is higher than that of the control class. So that students' understanding of mathematical concepts using the Group Investigation learning model is better than students using conventional learning models.